Program unit 9 - emotional competence – social emotional skills - Veiga-Branco, Augusta (2018)
Social Emotional Skills – Goldstein (1989) identify this group of capacities as basics, advanced, related to feelings, alternatives to aggression, coping with stress and planning skills. Assertiveness – or assertive language, means to be able to defend owns rights without manipulations. Active Listening – listen accurately with effective communication, empathy and no judgment of values